Posterior circulation strokes - Clinico-Radiological features and predictors of outcome at 6 months - Anju Susan Jacob; Sanjith Aaron; Sunithi Mani; Kundavaram Paul Prabhakar Abhilash; Ajay Kumar Mishra; Samuel George Hansdak; Ramya Iyyadurai; Alice Joan Mathuram; Sheena Evelyn Ebenezer; Mahendri V Narayana; Visalakshi Jeyaseelan; Thambu David Sudarsanam (Wolters Kluwer Medknow Publications, 2023)
Introduction: Posterior circulation stroke (PCS) is often diagnosed late and long-term outcomes have not been described in South India. We wished to study clinical features, long-term outcomes, and independent predictors of the same. Materials and Methods: We conducted a prospective cohort study in PCS patients from January 2014 to May 2017. Morbidity and mortality at discharge, at 3 months and 6 months was studied. Univariate and multivariate analysis of predictors of poor outcome as well as the survival analysis was computed. Results: We recruited 291 PCS during the study period; prevalence of PCS among all strokes was 12.9% in 2014. The mean age was 53.34 years (standard deviation 13.34). Young strokes constituted 28.8%. The common comorbidities were hypertension 72%, diabetes mellitus 52.6%, smoking 38.5%, and dyslipidemia 32.6%. The common presenting symptoms were giddiness 79%, unsteadiness 75.35%, ataxia 56%, motor deficits 48.8% and nausea and vomiting 43%. Most were Ischemic strokes (86.5%); 10.3% gave a history of preceding TIAs. Common arteries involved were posterior cerebral 45%, posterior inferior cerebellar 38%, and basilar artery 19.2%. Among ischemic strokes, large artery atherosclerosis was 50.8%. Dysphagia was seen in 32.6% and sepsis in 19.2%; post stroke pain in 23%, followed by cognition decline in 10.3%. Bad outcome (modifies Rankins score 4-6) was 16.8% at discharge, 16.4% at 1 month, 14.4% at 3 months, and 13.8% at 6 months. Independent predictors of bad outcomes at 6 months were baseline National Institute of Health Stroke Scale (NIHSS) score (Odds ratio [OR] 1615.59 confidence interval [CI] 27.64-94447.7), invasive ventilation (OR 7.77 CI 1.57-38.43), sepsis (OR 17.22 CI 1.45-204.08), and basilar artery involvement (OR 19.98 CI 1.67-238.81). Baseline NIHSS scores between 0 and 5 suggest a good outcome while scores more than 13 suggest a bad outcome at 6 months. At 6 months, half are unemployed. Conclusions: The prevalence, clinical features, and comorbidities were also similar to previous studies. There was good survival at 6 months. NIHSS score is useful in predicting poor outcomes.